Shumēru toshikokka no rōdōsoshiki ni tsuite – Bau-shinden to jiyūjin oyobi dorei tono kankei o chūshin ni - Yamamoto, Shigeru (1961)
A Study in the Social Organization of the Bau-Temple at Lagash – About the Relation of lú–kur6–dab5–ba with other Free-men and Slaves.